Methodological insights into intervention and outcomes in randomised controlled trials of herbal medicine for obesity: a scoping review - Janice Sue Wen Chan; Mei Siu Lau; Siti Hajar Muhamad Rosli; Siti Khadijah Mustapha Kamal; Wan Nurul Nadia Wan Seman; Nurul Hidayah Ali; Terence Yew Chin Tan; Ida Farah Ahmad; Puspawathy Krishnan; Marisa Khatijah Borhan; Ami Fazlin Syed Mohamed; Xin Yi Lim (Therapeutic Advances in Chronic Disease)
Background: With rising obesity rates worldwide, clinical trials focused on identifying effective treatments are increasing. While guidelines exist for pharmaceutical drugs targeting obesity, there are none for herbal medicine clinical trials for anti-obesity. Both industries refer to the same guidelines for clinical trials. Objectives: This scoping review aimed to gather information from herbal medicine anti-obesity randomised controlled trials (RCTs), analyse the methodologies and assess their alignment with international guidelines. Eligibility criteria: This review included RCTs of participants of all ages with obesity utilising herbal medicine with any comparators and focusing on various outcome measures. Sources of evidence: Only published journal articles were included. Charting methods: Articles were extracted from MEDLINE, CENTRAL and EMBASE using predetermined keywords. Relevant data, such as the study characteristics, types of herbal interventions and controls, treatment durations, outcome measures and safety monitoring methods were recorded in a table format for comparative analysis. Results: We included 99 RCTs that showed participant sample sizes ranging from 8 to 182, ages 18 to 80 years and body mass indexes (BMIs) between 25 and 49.9 kg/m 2 . Herbal interventions used single herbs ( n = 57) and mixtures ( n = 42), given for 14 days to 56 weeks. Studies implementing diet modifications include restricted calorie diets ( n = 35), food-portion controlled diets ( n = 7) and fixed calorie diets ( n = 7). Of the 28 studies implementing exercise, most were of moderate intensity ( n = 22). All studies collected BMI and weight as primary outcomes. Body fat composition was measured in over 50% of studies using a body analyser ( n = 57). Waist, hip and abdominal circumferences were infrequently measured. Radiological tools used include dual-energy X-ray absorptiometry ( n = 16), computed tomography scans ( n = 10) and ultrasound ( n = 2). Safety monitoring methods were reported in most studies ( n = 76). Conclusion: In conclusion, almost 50% of the studies adhered to international pharmaceutical clinical trial guidelines, addressing dietary, lifestyle, physical activity and cardiovascular risk factors. Nonetheless, more herbal anti-obesity studies need to consider the assessment of weight maintenance.